Logarithmic convexity of the eigenfunction of the Hessian operator in the ball - Ye, Yunhua (International Journal of Advanced Mathematical Sciences, 2015)
This paper is concerned with the logarithmic convexity of the eigenfunction of the Hessian operator. It is proved that the logarithm of the eigenfunction of the Hessian operator is strictly convex in the ball.